Sequência didática sobre os conceitos e fenômenos físicos relacionados com os eventos atmosféricos e meteorológicos para o ensino de física no 2º ano do ensino médio do município de Tefé - Bacelar, Reginaldo José Gonçalves (2016)
This paper proposes a teaching tool, based on the construction of a Rain Gauge from alternative materials, in order to facilitate meaningful learning, allowing high school students to understand the concepts and physical phenomena and their relationship to the main phenomena atmospheric and weather with the problem of how to contextualize the process of teaching learning of the main meteorological phenomena in the thematic area of the curriculum component of Physics Heat and Temperature, as the rain and its cycles, pressure, volume, maximum and minimum temperature, relative humidity donate. The product of this work is the development of a didactic sequence composed of teaching strategies as viewing videos, scientific texts, reading popular science articles and reconstruction of two physics experiments for data collection by students and discussion in group mode the physics teachers that teach the sophomore high school students can use in the classroom, in relation to the thematic area temperature and heat so that they can make the content from the previous knowledge of students and their importance in the region where they live. The methodological approach was guided by the theory of meaningful learning or assimilative of David Ausubel and the proposal is in line with the curriculum reform, established by the National Curriculum Guidelines for Secondary Education (PCNEM), suggesting a focused teaching to train entered citizens in society. We also highlight that were essential for the development of the didactic sequence: the application of investigative questionnaires for students and teacher classroom holder in which we identify the prior knowledge of the main atmospheric phenomena that enabled us to verify the conceptual changes of students in relation to the axis theme mentioned above.